Hubungan Efikasi Diri dengan Perilaku Mencontek - Devi Kusrieni (Universitas Ahmad Dahlan, 2014)
This study aims to determine the relationship between self-efficacy with cheating behavior in class X SMA Negeri 4 Yogyakarta in Academic Year 2014/2015. This research is a correlation. The population in this study were students of class X SMA Negeri 4 Yogyakarta in Academic Year 2014/2015. Subjects numbered 65 students out of a population of 260 students, making the subject of research carried out by random sampling technique. Instruments in this study using a questionnaire. The results of this study showed that self-efficacy against cheating behavior in class X SMA Negeri 4 Yogyakarta coined the roles of 21.3% and the remaining 78.7% of cheating behavior is caused by other variables outside of self-efficacy as procrastination, peer pressure, and pressure from parents. This study to conclude that there is a negative relationship between self-efficacy with cheating behavior in class X SMA Negeri 4 Yogyakarta academic year 2014/2015. Information from this research can serve as a basic reference program development guidance and counseling services to help students develop self-efficacy in minimizing the cheating behavior.